2013
DOI: 10.1017/s1461145713001004
|View full text |Cite|
|
Sign up to set email alerts
|

Early stress evokes temporally distinct consequences on the hippocampal transcriptome, anxiety and cognitive behaviour

Abstract: The early stress of maternal separation (ES) exerts long-lasting effects on cognition and anxiety. Recent evidence indicates enhanced hippocampus-dependent spatial learning in young adult ES animals, which shifts towards a decline in long-term memory in middle-aged life. Further, we find that ES animals exhibit enhanced anxiety in young adulthood that does not persist into middle-aged life. Here, we demonstrate unique, predominantly non-overlapping, hippocampal transcriptomes in young adult and middle-aged ES … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 64 publications
0
39
0
Order By: Relevance
“…that lead to more condensed chromatin structure-in the murine brain (Levine et al, 2012;Tesone-Coelho et al, 2015). Suri et al suggested an age-dependent expression of histone-modifying enzymes in response to early life stress with a decreased expression in young animals and an increased expression in adult mice when exposed to early life stress (Suri et al, 2014). This opposite expression of HDACs over time was consistent with distinct global mRNA expression profiles separating young from adult animals exposed to early life stress.…”
Section: Neuronal Activation Leading To Post-translational Modificatimentioning
confidence: 88%
“…that lead to more condensed chromatin structure-in the murine brain (Levine et al, 2012;Tesone-Coelho et al, 2015). Suri et al suggested an age-dependent expression of histone-modifying enzymes in response to early life stress with a decreased expression in young animals and an increased expression in adult mice when exposed to early life stress (Suri et al, 2014). This opposite expression of HDACs over time was consistent with distinct global mRNA expression profiles separating young from adult animals exposed to early life stress.…”
Section: Neuronal Activation Leading To Post-translational Modificatimentioning
confidence: 88%
“…The reduction in hippocampal volume observed in response to adolescent stressors is a cumulative consequence of decreased developmental growth of the hippocampal CA1, CA3 and DG cell layers (Isgor et al, 2004). Lehmann et al, 1999;Huot et al, 2002;Roceri et al, 2002;Pickering et al, 2006;Aisa et al, 2008Aisa et al, , 2009Monroy et al, 2010;Oomen et al, 2010Oomen et al, , 2011Leslie et al, 2011;Herpfer et al, 2012;Suri et al, 2013Suri et al, , 2014 Caldji et al, 1998;Weaver et al, 2002;Bredy et al, 2003;Menard et al, 2004;Champagne et al, 2008;Bagot et al, 2009 Low nesting material Decreased dendritic spines in CA1 neurons, CA1 neuronal dendritic atrophy Impaired CA3-commissural/ associational LTP. Impaired SC-CA1 LTP in middle-aged life Impaired hippocampaldependent spatial memory in young adulthood and middleaged life.…”
Section: Early Life Stress and Hippocampal Neuronal Damagementioning
confidence: 99%
“…Animals that receive low maternal care in postnatal life exhibit fewer excitatory synapses in the CA1 and CA3 subfields of the hippocampus with a concomitant reduction in the number of inhibitory synapses in the CA3 subfield (Wang et al, 2011b). In maternally separated animals, the hippocampal expression of multiple NMDA receptor subunits (NR2A, NR2B), AMPA receptors subunits (GluR1, GluR2) and metabotropic glutamate receptor mGluR4 is reduced, thus possibly influencing stoichiometry of glutamatergic receptors and glutamatergic receptor-driven electrophysiological responses and signaling (Roceri et al, 2002;Pickering et al, 2006;Martisova et al, 2012;O'Connor et al, 2013;Suri et al, 2014).…”
Section: Early Life Stress and Hippocampal Ltpmentioning
confidence: 99%
“…The age and species of the animals studied may also be a factor despite the brain region studied. For example, a study in the rat hippocampus showed significant increases in mRNA levels in HDAC 2 between 2 and 15 months of age (Suri et al, 2014). In the present study, the density of HDAC2+ PN showed a similar significant increased from 11-14 months of age but then significantly decreased between 14-19 months of age (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…3). Should the age of the animals in the study of Suri et al (2014) been extended to 19 months of age, it is possible that a decline in HDAC 2 may have occurred in hippocampal neurons making age a more critical factor than neuronal type.…”
Section: Discussionmentioning
confidence: 99%